Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter 9 - Review Exercises - Page 1036: 58


See one possible answer below.

Work Step by Step

Step 1. Given $y=x^2+6$, we can assume $x=t$ and thus $y=t^2+6$ Step 2. We can also assume $x=\sqrt 6\ tan(t)$ and thus $y=(\sqrt 6\ tan(t))^2+6=6tan^2t+6=6sec^2t$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.